Sosialisasi dan Pendampingan Pembuatan Lilin Aromaterapi Dari Limbah Minyak Jelantah di Desa Kaliangsana, Subang, Jawa Barat - Citra Faiza; Nurul Huda Jannah; Assyifa Sya’bani; Dene Herwanto (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Cooking oil is an important medium for processing food ingredients by frying. The need for cooking oil in Indonesia is increasing every year because almost all food processing in Indonesia uses cooking oil. The repeated use of cooking oil for all types of processes must be limited due to a decrease in the quality of the oil. This causes the oil cannot be used repeatedly because it can have an impact on health conditions. Therefore, there is a buildup of cooking oil waste that is no longer suitable for use or can be called used cooking oil. Kaliangsana Village, Kalijati, Subang is located close to the industrial area in Subang, so many housewives are looking for opportunities by opening food stalls at home. Thus, a lot of used cooking oil is wasted from the results of the culinary industry. Considering these conditions, the disposal of used cooking oil into the environment can create damage so that it is necessary to manage used cooking oil into products that have selling value. In this community service program, we educate the community regarding the management of used cooking oil into aromatherapy candle innovation products. The use of used cooking oil in addition to reducing environmental pollution can help the family economy